Gaya Hidup Bersih Dan Sehat Di Sekolah Dasar - Sastri Dalila Siregar; Ratika Balqis Nst; Nur Hafni Bahri Siambaton; Usiono Usiono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
A clean and healthy lifestyle is a health behavior that is realized through caring for oneself, family members and other people in the environment. Cultivating a healthy lifestyle is not just about washing hands, but throwing away rubbish so that students are exposed to a clean and healthy lifestyle. The researcher aims to conduct a literature review regarding clean and healthy lifestyles in elementary schools. Several PHBS programs researched from various articles show that clean and healthy lifestyles include washing hands, exercise, healthy snacks and proper waste disposal. Researchers used a technique (Systematic Literature Review). The target of this research is elementary school educators, because teacher awareness in educating children to behave in a clean and healthy lifestyle is still low. From the results of this research, it is hoped that teachers can teach and introduce clean and healthy lifestyles to children and provide several supporting services in implementing PHBS.